Where is your Stockholm? - Giusti, Matteo; Barthel, Stephan; Samuelsson, Karl (Stockholm University, 2017)
"Where is your Stockholm?" ("Var är ditt Stockholm?") is the first Public Participatory GIS (PPGIS) survey to address emotional, social, and environmental qualities at once. The social-ecological picture of Stockholm that emerges from the data can be used for a variety of different purposes; from analysis of everyday routines, to where people in Stockholm connect to the green infrastructure.

Purpose:

The dataset aims to describe positive and negative experiences that exist in the landscape of Stockholm together with social, environmental and psychological attributes. Because all datapoints are geographically mapped using GIS, this dataset provides a social-ecological understanding of Stockholm.

Studie "Var är ditt Stockholm" är en Public Participatory GIS (PPGIS) surveyundersökning kring emotionella, sociala och miljörelaterade aspekter. Den socioekonomiska bilden av Stockholm som framgår av data kan användas för en rad olika ändamål. från analys av vardagliga rutiner, till där människor i Stockholm ansluter till den gröna infrastrukturen.
Var är ditt Stockholm?
Keywords: natural environment; naturmiljö; urban environment; stadsmiljö; nature experience; naturupplevelse; connection to nature; relation till natur; Public Participatory GIS; Public Participatory GIS; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Natural Sciences; Naturvetenskap; Social Sciences; Samhällsvetenskap